2018
DOI: 10.1029/2018je005750
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Comet Siding Spring's Meteors on the Martian Atmosphere and Ionosphere

Abstract: On 19 October 2014, comet C/2013 A1 (Siding Spring) had a close encounter with Mars and deposited cometary dust particles into the Martian atmosphere. We report a comprehensive analysis of the resulting meteor shower and its perturbation on Mars' atmosphere and ionosphere. Using Mars Atmosphere and Volatile EvolutioN/Imaging Ultraviolet Spectrograph observations of ablated meteoric metallic species, we show this shower lasted less than 3 hr and was therefore limited to one hemisphere. Meteoric ablation occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 56 publications
4
40
0
Order By: Relevance
“…This paper has shown in situ electron density observations of the Northern Hemisphere at CA, while previous studies have shown other aspects of the encounter, such as in situ effects of cometary dust in the Southern hemisphere and subsequent redistribution of the dust by atmospheric circulation during the following days after the encounter (e.g., Crismani et al, 2018;Gurnett et al, 2015), the large variability of cometary magnetic field (e.g., Espley et al, 2015), and the shower of energetic particles that the comet produced over Mars (e.g., Sánchez-Cano et al, 2018). This paper has shown in situ electron density observations of the Northern Hemisphere at CA, while previous studies have shown other aspects of the encounter, such as in situ effects of cometary dust in the Southern hemisphere and subsequent redistribution of the dust by atmospheric circulation during the following days after the encounter (e.g., Crismani et al, 2018;Gurnett et al, 2015), the large variability of cometary magnetic field (e.g., Espley et al, 2015), and the shower of energetic particles that the comet produced over Mars (e.g., Sánchez-Cano et al, 2018).…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…This paper has shown in situ electron density observations of the Northern Hemisphere at CA, while previous studies have shown other aspects of the encounter, such as in situ effects of cometary dust in the Southern hemisphere and subsequent redistribution of the dust by atmospheric circulation during the following days after the encounter (e.g., Crismani et al, 2018;Gurnett et al, 2015), the large variability of cometary magnetic field (e.g., Espley et al, 2015), and the shower of energetic particles that the comet produced over Mars (e.g., Sánchez-Cano et al, 2018). This paper has shown in situ electron density observations of the Northern Hemisphere at CA, while previous studies have shown other aspects of the encounter, such as in situ effects of cometary dust in the Southern hemisphere and subsequent redistribution of the dust by atmospheric circulation during the following days after the encounter (e.g., Crismani et al, 2018;Gurnett et al, 2015), the large variability of cometary magnetic field (e.g., Espley et al, 2015), and the shower of energetic particles that the comet produced over Mars (e.g., Sánchez-Cano et al, 2018).…”
Section: Discussionmentioning
confidence: 80%
“…However, Crismani et al (2018) found in a comprehensive analysis that the meteor shower lasted less than 3 hr, was limited to one hemisphere and that horizontal winds globally redistributed this material over the next 2 days. However, Crismani et al (2018) found in a comprehensive analysis that the meteor shower lasted less than 3 hr, was limited to one hemisphere and that horizontal winds globally redistributed this material over the next 2 days.…”
Section: Dust Ablation In the Atmospherementioning
confidence: 98%
See 3 more Smart Citations